2015
DOI: 10.3892/ijo.2015.3022
|View full text |Cite
|
Sign up to set email alerts
|

TM4SF1 as a prognostic marker of pancreatic ductal adenocarcinoma is involved in migration and invasion of cancer cells

Abstract: Abstract. The cell surface protein Transmembrane 4 L6 family member 1 (TM4SF1) has been detected in various tumors, and its expression on tumor cells is implicated in cancer cell metastasis and patient prognosis. The role of TM4SF1 in malignant tumors remains poorly understood, particularly in pancreatic cancer. We performed immunohistochemical staining to analyze the expression of TM4SF1 in resected pancreatic tissues and investigated the correlation between TM4SF1 expression and prognosis. The function of TM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 37 publications
2
27
0
Order By: Relevance
“…The results suggested that TM4SF1 was a tumor suppressor in GC progression and invasion. Similar result was also obtained in the study that showed contribution of TM4SF1 loss to the invasion and migration of pancreatic cancer cells . However, other study showed that high expression of TM4SF1 is correlated with T stage, TNM stage, lymph node metastasis status of MIBC (muscle invasive bladder cancer) patients .…”
Section: Discussionsupporting
confidence: 86%
“…The results suggested that TM4SF1 was a tumor suppressor in GC progression and invasion. Similar result was also obtained in the study that showed contribution of TM4SF1 loss to the invasion and migration of pancreatic cancer cells . However, other study showed that high expression of TM4SF1 is correlated with T stage, TNM stage, lymph node metastasis status of MIBC (muscle invasive bladder cancer) patients .…”
Section: Discussionsupporting
confidence: 86%
“…Upregulated expression of TM4SF1 in lung cancer cells significantly increased their invasiveness in vitro and significantly decreased the survival time of xenograft mice, whereas silencing of TM4SF1 greatly inhibited tumor cell migration and invasion (Kao et al, 2003). Another study showed that decreased TM4SF1 expression enhanced the migration and invasion of pancreatic tumor cells in vitro (Zheng B. et al, 2015). In addition, silencing of TM4SF1 decreased the odds of lung and liver metastases in orthotopic pancreatic cancer (Cao et al, 2016).…”
Section: Tm4sf1 Promotes Cancer Proliferation and Migrationmentioning
confidence: 96%
“…Higher level expression of TM4SF1 was involved in GC tissues of higher grade differentiation. In addition, Zheng B. et al (2015) reported that patients with high levels of TM4SF1 showed longer survival time than those with low TM4SF1 levels. In vitro, reduced TM4SF1 expression after TGF-ß1-induced EMT enhanced the migration and invasion of pancreatic cancer cells partially via decreased E-cadherin expression.…”
Section: Clinical Prognosis Of Tm4sf1 Expressionmentioning
confidence: 99%
“…TM4SF1 has been reported to be associated with many tumors invasion and metastasis [38, 39], but has not been reported in esophageal cancer. The results presented in this study showed that TM4SF1 overexpression significantly enhanced KYSE150 and KYSE180 cells invasion and migration.…”
Section: Discussionmentioning
confidence: 99%